Severe Shiga Toxin Producing E. coli Hemolytic Uremic Syndrome in a Child with COVID-19 - Parolin, Mattia; Nosadini, Margherita; Meneghesso, Davide; Longo, Germana; Partigiani, Nicola Bertazza; Mazza, Alessandro; Benetti, Elisa (Archives of Clinical and Medical Case Reports, 2022)
Background: Thrombotic Microangiopathy (TMA) is one of the hallmarks of Shiga toxin-producing E. coli hemolytic uremic syndrome (STEC+HUS), but it is also described in coronavirus-19 disease (COVID-19). Case: A 5-year-old girl was admitted to our Emergency with severe neurological involvement in STEC+HUS. She experienced encephalopathy, status epilepticus and respiratory distress that required nasotracheal intubation. Parents also reported fever and respiratory symptoms in the previous days. SARS-Cov2 PCR was positive both in nasopharyngeal swab and bronchoalveolar lavage. Based on the severe Central Nervous System (CNS) involvement and the concomitant COVID-19, we managed the patient both for HUS and SARS-Cov2 infection administering dexamethasone, eculizumab and a whole blood adsorber during renal replacement therapy. The patient gradually improved until complete renal and neurological recovery. Discussion: In HUS, the severity of acute kidney injury is mainly related to the magnitude of TMA. Moreover, the activation of alternative complement pathway, triggered by Shiga toxin, is linked to the severity of both renal and neurological disease. C3 consumption in our patient could be associated with the degree of CNS involvement, although additional features such as electrolyte imbalances and dehydration were lacking. Since COVID-19 can lead to TMA via complement activation, we speculated on the role of SARS-Cov2 in transforming STEC infection into HUS and exacerbating TMA, thus supporting the use of therapies rarely used in STEC+HUS. Conclusion: The case described could provide further evidence on the similarities of TMA pathophysiology in HUS and COVID-19.